Factors associated with unplanned pregnancy among pregnant women in Uganda - Makumbi, Fredrick; Ssebadduka, Peter; Musaba, Milton; Wandabwa, Julius; Kiondo, Paul (Nature Publishing Group UK, 2025)
Unplanned pregnancies significantly contribute to maternal morbidity and mortality especially in settings where the abortion law is restrictive. This study aimed to establish the prevalence and factors associated with unplanned pregnancy among women attending antenatal clinic in Uganda. This cross-section study was carried out from 31st January to 30th June 2023 at Kawempe national referral hospital in Uganda. Three hundred and eighty-four pregnant mothers gave information on socio demographic, health system and family planning factors. Bivariate and multivariable logistic regression was done to determine the factors associated with unplanned pregnancy. The prevalence of unplanned pregnancy was (130/384) 34%. Unplanned pregnancy was associated with: age 20–24 years (AOR;2.8, 95%CI:1.4–5.8) and 25–34 years (AOR = 3.9,95%CI = 2.6–10.2), urban dwelling (AOR = 3.9,95%CI = 2.2–7.5) monogamy (AOR = 3.6,95%CI = 2.1–6.9), jobless women (AOR = 4.2,95%CI = 2.4–8.9) spouse in an informal sector (AOR = 2.8,95%CI = 1.7–4.5) lack of family planning communication (AOR = 2.3,95%CI = 1.4–5.4), single women (AOR = 0.4,95%CI = 0.2–0.8), income of Uganda shillings ≥ 200,000 (AOR = 0.3,95%CI = 0.1–0.6) and Seventh day Adventist belief (AOR = 0.2,95%CI = 0.09–0.6). There was a high prevalence of unplanned pregnancy in this tertiary hospital, associated with maternal age, place of residence, family type, employment status, not discussing about family planning among spouses, marital status, family income and being of Seventh Day Adventist faith. A community-based study in both urban and rural settings is recommended.
Keywords: Unplanned pregnancy; Kawempe; Uganda